PERANAN TOSORA SEBAGAI PUSAT PEMERINTAHAN KERAJAAN WAJO ABAD XVI-XIX - Akin Duli (WalennaE, 2010)
The ruins of various building of Tosora site from the past is a silence witness of the glorious and decline story of the Kingdom of Wajo at the 16 to 19 century, which can be seen and observed at the present time.  These building consist of Mosque, Mushallah, Gaddong, Tombs, Forts, Ancient Well, Port, Canon and others artefacts such as ceramics, earthenware, metal-items and other. Based by that evidence of remaining items of the past which widely scattered within the Tosora site and its surrounding area, it can be referred as the witness of how the role of Tosora in the past time, as the center of government of the Kingdom of Wajo. Tosora was selected as the capital city of the Kingdom of Wajo due to its strategic location.Runtuhan bangunan situs Tosora dari masa lalu adalah saksi bisu dari kisah kejayaan dan kemunduran Kerajaan Wajo pada abad 16 hingga 19, peninggalan yang dapat diamati pada saat ini yaitu bangunan Masjid, Mushallah, Gaddong, Makam, Benteng, Sumur Kuno, Pelabuhan, Canon dan artefak lainnya seperti keramik, gerabah, logam dan lainnya. Berdasarkan artefak yang ditemukan dapat dijadikan bukti peran Tosora di masa lalu yaitu sebagai pusat pemerintahan Kerajaan Wajo, Tosora terpilih sebagai ibu kota Kerajaan Wajo karena lokasinya yang strategis.